Metacognition and executive functions: Developmental interrelations and interactions with cognitive performance in the preschool and primary school years - Smaragda Kazi; Alexandra Karousou; Angelos Markos; Dimitra Economacou; Tryfonas Bikos; Nikos Makris (Ψυχολογία: το Περιοδικό της Ελληνικής Ψυχολογικής Εταιρείας)
A large body of research highlights the important role of both executive functions (EF) and metacognitive monitoring (MM) in children's cognitive functioning in general, and in their performance on specific cognitive tasks in particular. Recent approaches suggest that EF and MM constitute different expressions of cognitive self-regulation. Despite the theoretical interest, there has been limited research on the complex interactions between EF, MM, and cognitive performance. In this paper, we study the relationship between EF and MM and their association with cognitive performance in mathematical and spatial problem-solving while taking into account children's age and performance in a fluid intelligence task. Specifically, based on a sample of 277 children aged 4 to 11 years, two alternative hypotheses are explored: (1) Cognitive performance mediates the relationship between EF and MM, and (2) MM mediates the effect of EF on cognitive performance. The results highlight the relationship between some aspects of these two theoretical constructs and their effect on children's cognitive performance. MM emerged as a significant mediator in the relationship between EF and cognitive performance. The alternative hypothesis was not supported. Results are discussed on the basis of previous studies on the development of metacognitive monitoring and executive functions.